2014
DOI: 10.1158/0008-5472.can-13-2699
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis of Formalin-Fixed Prostate Cancer Specimens Identifies Biomarkers of Disease Recurrence

Abstract: Prostate cancer remains the second leading cause of cancer death in American men and there is an unmet need for biomarkers to identify patients with aggressive disease. In an effort to identify biomarkers of recurrence, we performed global RNA sequencing on 106 formalin-fixed, paraffin-embedded (FFPE) prostatectomy samples from 100 patients at three independent sites, defining a 24-gene signature panel. The 24 genes in this panel function in cell cycle progression, angiogenesis, hypoxia, apoptosis, PI3K signal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 43 publications
3
130
0
Order By: Relevance
“…Molecular biomarkers are a promising class of prognostic biomarker candidates, but these studies in prostate cancer have been limited by follow-up insufficient for study of metastatic progression or survival because of the long disease course (16). Separately, outlier analysis has identified preeminent prostate cancer genes TMPRSS2-ERG fusions and SPINK1 (19,20), but has been limited to comparisons of cancer versus normal samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular biomarkers are a promising class of prognostic biomarker candidates, but these studies in prostate cancer have been limited by follow-up insufficient for study of metastatic progression or survival because of the long disease course (16). Separately, outlier analysis has identified preeminent prostate cancer genes TMPRSS2-ERG fusions and SPINK1 (19,20), but has been limited to comparisons of cancer versus normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic studies in prostate cancer are hampered by the long disease course, resulting in follow-up of insufficient length to study associations with the most meaningful outcomes of metastatic progression, prostate cancer death, and overall survival. Thus, many studies have been limited to the intermediate outcome of biochemical recurrence (16).…”
Section: Introductionmentioning
confidence: 99%
“…4 This includes several studies in prostate cancer, which are in agreement with the findings of Di Sante et al 5 Furthermore, chemical inhibition of SIRT1 in prostate cancer has been shown to reduce cellular growth, viability, and chemoresistance, and a recent analysis of prostate cancer tissues showed SIRT1 to be a reliable biomarker of disease recurrence. 6 It would be logical to conclude from these findings that SIRT1 has a tumor promoter function in prostate cancer. However, Di Sante et al 5 have found that in prostate cancer patients, a low level of SIRT1 is associated with decreased recurrence-free survival, supporting a tumor suppressor function of SIRT1 in prostate cancer.…”
Section: Sirt1 As An Oncogene or Tumor Suppressor In Cancermentioning
confidence: 99%
“…We performed RNA sequencing on prostatectomy samples from 100 patients and identified a new set of biomarkers of biochemical recurrence composed of a 24-gene panel. 82 This panel showed significant improvement of prediction of biochemical recurrence over clinical parameters alone and over previously described biomarker panels based on cellular proliferation. 83 The findings were especially significant in demonstrating that RNAseq analysis of formalinfixed, paraffin-embedded prostate cancer specimens is feasible and can provide critical insights into the mechanisms of prostate cancer progression that may be translated into clinically useful biomarkers, which can then be used in institutions and settings that may not have access to frozen, banked specimens.…”
Section: Tumors With Spindle Cell Morphologymentioning
confidence: 79%
“…83 The findings were especially significant in demonstrating that RNAseq analysis of formalinfixed, paraffin-embedded prostate cancer specimens is feasible and can provide critical insights into the mechanisms of prostate cancer progression that may be translated into clinically useful biomarkers, which can then be used in institutions and settings that may not have access to frozen, banked specimens. 82 …”
Section: Tumors With Spindle Cell Morphologymentioning
confidence: 99%